The Acid-Activated Sand Potentially Ameliorates Water Calcium Content - Hermania Em Wogo; Yoseph J. Hema; Suwari (Journal of Applied Chemical Science, 2013)
The sand activation using three types of acids namely HNO3 0.1 M, H2SO4 1 M, and H3PO4 14 M have been done. The acid-activated sand was used as adsorbent of calcium ions (Ca2+) contained in hard water. The study was firstly determined the chemical contents of the sand using Energy Dispersive Xray Fluorescence instrument and followed by determination of the sand surface area using methylene blue and it’s surface acidity by titration. The experiment conducted with absence of the acid was carried out as an control. The results showed that the sand contained 47.95 % of SiO2 and 18.79% of Fe2O3. The highest surface area was found at the sample activated by H3PO4 14 M (27.73 m2/g). The surface area activated by H2SO4 1 M and HNO3 0.1 M were 26.56 and 25.59 m2/g, respectively. Highest surface acidity was found at the sample activated by H3PO4 14 M (299.60 µmol/gram), while those treated with H2SO4 1 M and HNO3 0.1M were 277.70 and 204.80 µmol/gram, respectively. That was, however, the sample without acid activation had surface acidity of 113.60 µmol/gram. Furthermore, the sand activated by H3PO4 14 M maximally absorbed 892.86 μmol Ca/g sand and those activated by H2SO4 1 M and HNO3 0.1M maximally absorbed 847.46 and 684.93 μmol Ca/g sand, respectively; whereas the sand without activation maximally absorbed 510.20 μmol Ca/g sand. Those results indicate that higher surface area higher surface acidity and higher capability of the calcium ion absorptions. Therefore, the acids-activated sand potentially reduces calcium ions content of hard water.